2012
DOI: 10.5551/jat.11940
|View full text |Cite
|
Sign up to set email alerts
|

FTO, Abdominal Adiposity, Fasting Hyperglycemia Associated with Elevated HbA1c in Japanese Middle-Aged Women

Abstract: Aim: FTO is the most important polygene for obesity and type 2 diabetes. Our aims were to investigate whether a variant in FTO affects glucose dysregulation through its effect on fat accumulation or distribution, and when and how FTO influences fat accumulation and distribution and glucose dysregulation from birth until midlife. Methods: A total of 454 Japanese female university students (mean age: 20 years) and 132 middleaged women (mean age: 50 years) who were the biological mothers of the students underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 38 publications
4
70
0
1
Order By: Relevance
“…The mean hsCRP of the subjects was 1.3 ± 2.9 mg/L, and 9.8% of the subjects were in the high risk hsCRP group, which was similar to the level in young Indian (mean hsCRP levels, 1.3 ± 2.5 mg/L, 12.8% of subjects belonged to the high risk group) [11], but higher than that of other Asian young women [39,40] and Turkish women [41] as well as young women in European countries (mean hsCRP levels, 0.67-0.89 mg/L) [42,43]. In our subjects, hsCRP was highly correlated with many of the metabolic disease parameters such as BMI, WHR, body fat, blood pressure, white blood cell count, triglycerides, and HDL cholesterol, confirming the results of other studies, mostly in middle-aged populations [44,45].…”
Section: Discussionsupporting
confidence: 53%
“…The mean hsCRP of the subjects was 1.3 ± 2.9 mg/L, and 9.8% of the subjects were in the high risk hsCRP group, which was similar to the level in young Indian (mean hsCRP levels, 1.3 ± 2.5 mg/L, 12.8% of subjects belonged to the high risk group) [11], but higher than that of other Asian young women [39,40] and Turkish women [41] as well as young women in European countries (mean hsCRP levels, 0.67-0.89 mg/L) [42,43]. In our subjects, hsCRP was highly correlated with many of the metabolic disease parameters such as BMI, WHR, body fat, blood pressure, white blood cell count, triglycerides, and HDL cholesterol, confirming the results of other studies, mostly in middle-aged populations [44,45].…”
Section: Discussionsupporting
confidence: 53%
“…Genotyping of the SNP was performed using TaqMan SNP Genotyping Assays (Applied Biosystems, Foster City, CA, USA) or a multiplex-polymerase chain reaction (PCR)-invader assay, as described previously [25,29]. In this study, we selected four SNPs (rs8050136, rs9939609, rs1121980, and rs1558902) in the FTO locus; these were the most frequently analyzed SNPs at this locus in the Japanese population [1620,3034]. Previous studies have demonstrated that rs8050136, rs9939609, and rs1558902 are in high linkage disequilibrium (LD) with each other and were repeatedly associated with obesity or type 2 diabetes in different ethnicities [31,33,34].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we selected four SNPs (rs8050136, rs9939609, rs1121980, and rs1558902) in the FTO locus; these were the most frequently analyzed SNPs at this locus in the Japanese population [1620,3034]. Previous studies have demonstrated that rs8050136, rs9939609, and rs1558902 are in high linkage disequilibrium (LD) with each other and were repeatedly associated with obesity or type 2 diabetes in different ethnicities [31,33,34]. First, we examined the LD among these three SNPs in our Japanese population and confirmed that these three SNPs were in absolute LD ( r 2 = 0.99) in our population (S2 Table).…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated routine chemical parameters, including liver enzymes, glucose, insulin, lipids, and lipoproteins, as previously reported [14, 15] and insulin resistance was evaluated using homeostasis model assessment (HOMA-IR) [16]. …”
Section: Participants and Methodsmentioning
confidence: 99%
“…Adipokines and inflammatory markers were measured as previously reported [14, 15]. They included adiponectin, leptin, plasminogen activator inhibitor-1 (PAI-1), preheparin lipoprotein lipase (LPL), high-sensitivity C-reactive protein (hsCRP), interleukin-6 (IL-6), and tumor necrosis factor-1 (TNF- α ).…”
Section: Participants and Methodsmentioning
confidence: 99%